Nicaraguan Migrants in Costa Rica - M. Marquette, Catherine (2006)
This document is the executive summary of a detailed document entitled, Nicaraguan Migrants and Poverty in Costa Rica, which was prepared for the World Bank in 2006. The more detailed background paper from which this summary is derived was commissioned as a background paper in preparation for an upcoming poverty mission by the World Bank to Costa Rica. This summary and the larger document from which it comes provides: (1) a general overview of the socioeconomic and health situation of Nicaraguan migrants in Costa Rica and (2) a review of the poverty characteristics of these migrants. The primary data sources for the larger paper were successive recent rounds of the Annual National Household Survey in Costa Rica and the 2000 Census. The more detailed report on which this summary is based also reviews issues of data quality, comparability, and methodological problems with respect to existing information on Nicaraguan migrants in Costa Rica. As a summary, the document below, does not include detailed citations, which are of course included in the larger report. Readers are thus, referred to the larger report for citations and more detailed information on the data included in this summary.